AVIZINHANDO EXPERIÊNCIAS: HISTÓRIAS DE UMA CIDADE COM A LOUCURA - Monecchi, Samara Pimenta (2021)
This work aims to tell stories of experiences with madness in a city. The city, which in this research tells some of its countless stories, is Cariacica, chosen to host the first public psychiatric hospital in Espírito Santo state, Adauto Botelho Hospital